Listening is Action: A Soundwalk with Hildegard Westerkamp - Luis Velasco-Pufleau (Performance Philosophy, 2023)
In the sound documentary Listening is Action, the composer Hildegard Westerkamp engages in a conversation with Luis Velasco-Pufleau at her home in the city of Vancouver, which is situated on the traditional, ancestral, and unceded territories of the xʷməθkʷəy̓əm (Musqueam), Sḵwx̱wú7mesh (Squamish), and səlilwətaɬ (Tsleil-Waututh) Nations. She talks us through her first field recordings and her soundwalking practice, her work at the Vancouver Co-operative Radio, and her participation in the World Soundscape Project, all of which started or took place in the 1970s. Furthermore, she takes us on soundwalks at places she used to go and record more than thirty years ago, such as those now called Kitsilano Beach and Vancouver’s Downtown Eastside, and that constitute the sources for her soundscape works A Walk Through the City (1981) and Kits Beach Soundwalk (1989). This sound documentary is an invitation to listen more attentively to the multiple voices that inhabit our environments in order to imagine new, plural, and unforeseen realities. The sound work Listening is Action is enhanced by a written commentary in which Luis Velasco-Pufleau explores the radical relationality of listening and the connection between Westerkamp’s thinking with the work of Pauline Oliveros and Hannah Arendt. Finally, he engages with critical listening positionality in order to reflect on some of the limits and contradictions present in the sound documentary.